A Multi-Component Treatment to Reduce Packing in Children With Feeding and Autism Spectrum Disorders. (November 2014) - Levin, Darren S.; Volkert, Valerie M.; Piazza, Cathleen C.
Despite the high prevalence and potential negative consequences of feeding disorders in children with autism spectrum disorder (ASD), there are surprisingly few studies that examine the efficacy of treatment exclusively with these children. Children with feeding disorders also frequently exhibit packing (holding or pocketing food without swallowing). Investigators have evaluated procedures in the general pediatric population to treat packing, and some have shown that procedures need to be combined to form an effective treatment. Although investigators have evaluated the efficacy of re-distribution, swallow facilitation, and a chaser, these procedures have not been evaluated specifically with children with ASD. Prior to the current investigation, we successfully used nonremoval procedures to increase acceptance of pureed foods and liquids and decrease the inappropriate mealtime behavior of two children diagnosed with ASD and feeding problems; however, in each case, packing emerged during initial treatment. We then used different combinations of re-distribution, swallow facilitation, and chaser treatments to decrease packing for both children.